The Digital Transformation of Traditional Culinary Businesses Towards Online Success - Andy Hakim (PT Agung Media Publisher, 2025)
The digital transformation of traditional culinary businesses has become a critical pathway for achieving sustainable growth and competitiveness in the digital age. This study explores how these businesses transition to online platforms, the challenges they face, and the benefits they achieve. A mixed-methods approach was employed, combining qualitative interviews with traditional culinary business owners and quantitative analysis of business performance data before and after digital adoption. The study also examined case studies of businesses successfully utilizing digital tools such as food delivery platforms, social media marketing, and AI-based analytics. Findings reveal that businesses adopting digital tools experience significant growth in revenue (up to 40%) from 2019-2024, improved operational efficiency, and enhanced customer engagement. However, challenges such as a lack of digital literacy and initial investment costs remain substantial barriers. Successful case studies demonstrate that leveraging partnerships with delivery platforms and effective social media marketing are key strategies for success. Digital transformation provides opportunities to widen market reach, preserve culinary heritage, and enhance customer experiences. To overcome barriers, governments and private organizations can play a role by offering training programs and financial support. The integration of advanced technologies like AI and data analytics also shows promise in driving efficiency and personalization. The digital transformation of traditional culinary businesses is not merely a trend but a necessity for long-term success. Despite challenges, the benefits of increased visibility, operational improvements, and customer satisfaction outweigh the costs, making digital adoption a viable strategy for traditional culinary enterprises.